The Determinant Factor Of E-Commerce User Satisfaction Mediated By Customer Experience - Ahmad Faydlurrahman Abdillah; Fajar Dipa Wiadnyana; Siroy Afandi; Arta Moro Sundjaja (Cakrawala Repositori IMWI, 2023)
The research is proposed to examine the determinant factors of e-commerce user satisfaction that mediated by customer experience in Indonesia. Some measurement items were adopted from existing literature. To get the result on how this affects the satisfaction, this research used a quantitative approach to descriptive analysis. This study uses 284 respondents in five e-commerce namely; Tokopedia, Shopee, Bukalapak, Blibli, JD.id, Lazada, and Zalora. The researchers distributed the questionnaire through social media and online messaging applications. Based on the demographic profile of respondents, the researchers discovered that the respondents are an educated person, work as professional employees or college students, and allocate more than once per week to shop on e-commerce platforms. The structural equation model developed in this study was tested using Partial Least Squares (PLS) to analyze data from 284 respondents. The results of the study found that the relationship between e-commerce innovation and e-commerce service quality have a positive impact on customer satisfaction that mediated by customer experience. This study was focused on relationship between e-commerce innovation, e-commerce service quality, customer experience, and customer satisfaction. Therefore, further research is expected to be able to test the determinants of the other factors.